Implementasi Keamanan Jaringan Metode Port Knocking dan Port Blocking Berbasis Mikrotik PT Securindo Packatama Indonesia - Ade Eksan Nuryakin (E-Jurnal Universitas Samudra, 2023)
Network security is important for a company or institution in maintaining data and information security. Often the computer network has problems in managing the computer network. Problems that arise can open up opportunities for irresponsible people to hack and damage the running network. In order to avoid misuse of computer networks by irresponsible people, it is necessary to increase network security that is more secure and stronger. In this research, research has been carried out to develop more secure network security by using port knocking and port blocking methods on Mikrotik. In this study, the author will explain the implementation of the port knocking method to provide filter access to the firewall, aiming to provide security for computer access users so that no party or party can change the configuration on the proxy so that network security is maintained. The final result of the study shows that authentication for ports so as to make the server safe and also other ports, closing ports to prevent access attacks from attackers who are not entitled to enter. By using port knocking and port blocking methods, the attacker will try harder to penetrate the system wall on the firewall.